Agricultural Risk Management and Land Tenure - Gregor Schwerhoff; Matthias Kalkuhl; Katharina Waha (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Farmers under a sharecropping contract have been shown to exert less effort than farmers renting land due to lower incentives. They do not only choose their effort level, however, but also make investment decisions between projects of different risk-return profiles. We develop a small theoretical model that integrates the effort effect of sharecropping as well as the risk-reducing aspect of sharecropping which allows analyzing the implications for production, risk-management and risk-coping. In the empirical analysis, we combine a household survey taken in eleven African countries with data on climate risk to test the theoretical predictions. We find that sharecropping is endogenous to climate: it is more frequent in regions with low rainfall and higher weather variability. In a second step we test whether sharecropping can function as a substitute to other risk adaptation strategies. We find that sharecropping farmers are less likely to own livestock and more likely to use fertilizer. In economies where formal kinds of insurance are unavailable, sharecropping thus functions as a form of insurance and reduces the need for potentially harmful risk management strategies.
Keywords: O13; Q12; Q15; 330